Statistical optimization for comparative hydrolysis and fermentation for hemicellulosic ethanolgenesis - Chaudhary, Asma; Aihetasham, Ayesha; Younas, Smavia; Basheer, Nimra; Hussain, Nageen; Naz, Sumaira; Aziz, Tariq; Albekairi, Thamer H. (Italian Journal of Food Science, 2024)
The concept of ‘Energy from waste’ is one of the most focused areas of work to find a solution for controlling trash and combat energy crises. In Pakistan and other agricultural countries, because of their substantial use during the summer, watermelon peels as fruit waste are usually thrown out as a trash. This study supported the management of huge quantities of waste to value-added products at a commercial scale. The current study aims to select and subject xylanolytic and ethanologenic Bacillus cereus XG2 for water melon peels valorization appropriately with comparison of three hydrolysis techniques. The study will be helpful for selection of economical and environmentally beneficial valorization strategies. For ethanalogenesis, separate hydrolysis and fermentation (SHF) protocols with Saccharomyces cerevisiae K7 and Metchnikowia cibodasensis Y34 were used. For hydrolysis, three different saccharification approaches, viz. dilute sulfuric acid, enzymatic hydrolysis (using Bacillus cereus XG2 xylanases), and combined acidic and enzymatic hydrolysis, were adopted. Two statistical models, Placket-Burman (hydrolysis) and Central composite design (ethanologenesis) were used. In untreated watermelon waste (WW), reducing sugar, total lipids, total carbohydrates, and protein contents were calculated as 16.70±0.05 g/L, 3.20±0.02 g/L, 28.7±0.04 g/L, and 3.70±0.03 g/L, respectively. Similarly, the lignin (15.51±0.22%), hemicellulose (17.20±2.30%). and cellulose (52.26±0.33%) contents were also analyzed. Based on the significance of the Plackett–Burman model for enzymatic saccharification, the released reducing sugars as well as total sugars were 21.62±0.01 g/L and 43.30±1.55 g/L, respectively, and enzymatic hydrolyzate was adopted for further fermentation experiments. By CCD model, the highest ethanol yield calculated for yeast Metchnikowia cibodasensis Y34 was 0.4±0.04 g/g of fermentable sugars at 32.5oC with 50% enzymatic hydrolysate of WW by incubating for 8 days. It was suggested that SHF could be a beneficial approach to increase the conversion of hemicellulose to fermentable sugars to produce bioethanol on a large scale.